Ecological Interface Design for Knee and Hip Automatic Physiotherapy Assistant and Rehabilitation System. Issue 1 (June 2014) - Li, Yeti; Burns, Catherine M.; Kulić, Dana
In this paper, we report on a recent interface design and evaluation process for a new knee and hip automatic physiotherapy assistant and rehabilitation system (ARS). Interface design was concurrent with the development of ARS. The ARS has the potential to improve the automation of rehabilitation treatments, by providing quantitative measures of a patient's motion. However, the complexity of rehabilitation information available to the therapist has increased with this additional information. We applied Ecological Interface Design (EID) to understand the domain of physiotherapy and the role of the automation. Results of a Work Domain Analysis (WDA) revealed new functions and constraints in rehabilitation now accessible through the ARS, and provided the design requirements for interface design. A novel interface was designed which is currently undergoing evaluation to see if it improves the quality and experience of physiotherapy. This study provides an example of the advantages of using EID at the early phase of design, and how to apply EID to a system of increasing automaticity.